Effect of palm stearin content on the properties of Injection Moulded 316L stainless steel powder - M. M., Noor; M. A., Omar; I., Subuki; K., Kadirgama; M. S. M., Sani; M. M., Rahman; Z., Hamedon (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.